Eu Activation in β-Ga2O3 MOVPE Thin Films by Ion Implantation. (1st January 2019) - Peres, M.; Nogales, E.; Mendez, B.; Lorenz, K.; Correia, M. R.; Monteiro, T.; Sedrine, N. Ben
Abstract : In this work, we have established the effects of Eu implantation and annealing on β -Ga2 O3 thin films grown by metal organic vapor phase epitaxy (MOVPE) on sapphire substrate. The study is based on the combined information from structural and optical techniques: X-ray diffraction (XRD), Rutherford backscattering spectrometry (RBS), cathodoluminescence (CL), photoluminescence (PL), and photoluminescence excitation (PLE). The thin films were implanted with a fluence of 1 × 10 15 Eu·cm −2 and annealed at 900°C. Neither significant changes in peak width or position nor additional peaks related to Eu complexes were detected in the XRD 2θ-ω scans. RBS results and SRIM simulation are in good agreement, revealing that no Eu diffusion to the surface occurs during annealing. For the used implantation/annealing conditions, the Eu ion penetration depth reached ∼130 nm, with a maximum concentration at ∼50 nm. Furthermore, CL and PL/PLE results evidenced the optical activation of the Eu 3+ in the β -Ga2 O3 host. The detailed study of the Eu 3+ intra-4 f shell transitions revealed that at least one active site is created by the Eu implantation/annealing in β -Ga2 O3 thin films grown on sapphire. Independently of the β -Ga2 O3 film thickness, well controlled optical activation of implanted Eu was achieved.